2015
DOI: 10.1590/0103-5150.028.004.ao02
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle strength and sexual function in women

Abstract: Introduction : Pelvic floor (PF) muscles react to sexual stimuli with increased local blood circulation and involuntary contractions during orgasm. The training of the PF musculature helps in the improvement of the female sexual function. Objective : To verify the association between PF muscle strength and sexual function in women, controlling age and parity. Method : Cross-sectional study based on associations. The study included women who attended a reference center in Florianópolis, Santa Catarina, for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…By contrast, a study in Belém, Pará state, Brazil assessing the possible relationship between female sexual function and the degree of PFM contraction in 20 to 40 year-old sexually active women indicated that the stronger the PFM contractions, the better the sexual function indices in healthy women [32]. Thus, women submitted to PFMT presented a significant improvement in sexual function scores on the FSFI questionnaire (in all domains and the total score) [24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…By contrast, a study in Belém, Pará state, Brazil assessing the possible relationship between female sexual function and the degree of PFM contraction in 20 to 40 year-old sexually active women indicated that the stronger the PFM contractions, the better the sexual function indices in healthy women [32]. Thus, women submitted to PFMT presented a significant improvement in sexual function scores on the FSFI questionnaire (in all domains and the total score) [24].…”
Section: Discussionmentioning
confidence: 90%
“…The levator ani, bulbocavernosus and ischiocavernosus muscles participate in female sexual response and function and they are responsible for the rhythmic and involuntary contractions that occur during orgasm. Thus, PFM function is an important attribute for female sexual function, as demonstrated in a study with women in Florianópolis, Santa Catarina state (SC), Brazil [24] Studies [25,26] suggest that PFM strength is related to sexual function, specifically orgasm and arousal. In this respect, women submitted to pelvic floor muscle training (PFMT) show a significant improvement in FSFI dimensions and total score [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The pelvic floor muscles play an important in sustaining blood flow to the penis to maintain erections [21,22]. These muscles keep a constant pressure on penile veins during sexual activity and prevent blood from leaving the area making the erection sustained and possible [23]. Kegel exercises for women to improve strength of pelvic floor muscles help in improving the sexual function in women.…”
Section: Discussionmentioning
confidence: 99%
“…Sacomori et al [25] avaliaram a associação da força dos MAP versus função sexual e concluíram que as mulheres que apresentaram força muscular considerada boa, tiveram significativamente maior desejo, excitação, lubrificação e orgasmo, comparado as que apresentaram menos força nos MAP, corroborando a conclusão de Lunardon e Brondani [13] em outro estudo.…”
Section: Discussionunclassified